Settle in Casablanca:The Case of MoulayRachid and Anfa districts - Zahli, Salah; Yahyaoui, Mostafa (Milev Journal of Research and Studies, 2021)
Most of the geographical literatures of the postmodern period, which are interested on the space and Wohnen, are based on the role of qualitative and ethnographic approach in the extraction of field results, indeed, it is one of the most important methods which focuses on the relationship of the individual and society with space, and which interested on the individual's lifestyle and spatiality as it is and not as it is audible or read. This article aims to study the affective relationship between the individual and the space through the concept of Wohnen, by focusing on the individual's social representations about the space in its comprehensiveness, also by focusing on the daily life of the individual through his spatial behaviors and his Wohnen, and all that is included in the geography of the daily life of individuals. The research will focus on the analysis of the dwelling's components with its individual, societal and spatial characteristics on the one hand, on the otherhand, the highlighting of the space's influence with its political, historical, economic symbolysm on the individual, by showing the disparity between the respondents in the district of Anfa and Moulay Rashid